The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.22219/jrak.v13i2.26790
|View full text |Cite
|
Sign up to set email alerts
|

The Islamic Religiosity And Financial Well-Being: A Moderated Mediation Model Of Financial Behavior And Literacy

Mulyadi Mulyadi,
Amelia Oktrivina,
Hendryadi Hendryadi
et al.

Abstract: Purpose: By testing a moderated mediation model, this study aims to examine the mediating role of financial behavior in the relationship between Islamic religiosity, financial behavior, and financial well-being. The study also examines if financial literacy moderates this effect. Methodology/approach: The PROCESS macros version 4.0 was used to assess the hypothesized model based on data from 247 college students. Findings: The findings show that Islamic religiosity influences students' effective financial beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
0
1
Order By: Relevance
“…Thus, it might be said that there is insufficient statistical evidence to support the eighth hypothesis. The findings of this study contradict those of (Mulyadi et al, 2023) who found that financial literacy moderates the association between Islamic religiosity and financial behavior. Thus, the beneficial effects of Islamic religiosity on prudent financial behavior and financial well-being are amplified when financial literacy is attained via higher education.…”
Section: The Moderating Effect Of Financial Literacycontrasting
confidence: 99%
“…Thus, it might be said that there is insufficient statistical evidence to support the eighth hypothesis. The findings of this study contradict those of (Mulyadi et al, 2023) who found that financial literacy moderates the association between Islamic religiosity and financial behavior. Thus, the beneficial effects of Islamic religiosity on prudent financial behavior and financial well-being are amplified when financial literacy is attained via higher education.…”
Section: The Moderating Effect Of Financial Literacycontrasting
confidence: 99%